The Strategy of Using PCMs in Building Sector Applications - Ruaa Ismail; Naglaa Megahed; Sara Eltarabily (Port Said Engineering Research Journal, 2022)
With the recent large increase in the building sector's energy use to provide thermal comfort to consumers, the restrictions of climate change, and the scarcity of energy supplies, there has been a need to develop ways to reduce energy consumption. The use of phase change materials (PCMs) as a thermal energy storage (TES) system has attracted a lot of attention as a technique to improve thermal performance, conserve energy, and improve occupant comfort. When storing energy via phase change, the key advantage in terms of building materials is the higher energy density, which indicates that more energy can be stored in a constant volume. This study focuses on the vital role of PCMs in building applications by presenting the different classifications of PCMs as well as their integration techniques, systems, and benefits for building applications. Different case studies for full scale buildings are presented. A design strategy is concluded for integrating PCMs in buildings.